PENGARUH PENGGUNAAN METODE MIND MAPPING DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SEJARAH - Khasanah Khasanah; Sopiyullah Taopik Anggun (Akademika, 2017)
The effect of Mind mapping Methods and Critical Thinking SkillsLearning and Outcomes History Of StudentsInLearning History (experimental studies InClass X Senior High School 1 Wanayasa Purwakarta). The purpose of this research was todetermine the effect of mind mapping methods of learning, critical thinking skills, and theresult of learning the history of high school students. This study uses a 2x2 factorial designexperiment with a sample of 40 students conducted in Senior High School 1 Wanayasa..These results of the research show that; (1) the outcomes of students from groups that aretaught using mind mapping higher than students taught by lecture method, (2) there is noeffect of significant interaction between instructional method and critical thinking skills ofstudents in the teaching of history, (3) students have the ability to think critically high andare taught by the method of mind mapping higher learning outcomes than students taught bylecture method, (4) students who have the ability to think critically low and is taught bylecture method higher learning outcomes than students taught by using mind mapping.Thisresearch shows the successful use of instructional methods. Therefore, teachers areexpected to be: (1) enhance the creativity and understanding of learning methods toimprove and train the critical thinking skills of students in learning the history, (2) providestudents the opportunity to be creative in making a map of concepts that they canunderstand, (3) train students more vigorous, active, creative history teaching so thatstudents can think scientific, logical, critical, and may find the concept of learning materialindependently